Managing Free Text for Secondary Use of Health Data - Griffon, N.; Charlet, J.; Darmoni, S. J.; Section Editors for the IMIA Yearbook Section on Knowledge Representation and Management (Yearbook of Medical Informatics, 2014)
Objective: To summarize the best papers in the field of Knowledge Representation and Management (KRM).Methods: A comprehensive review of medical informatics literature was performed to select some of the most interesting papers of KRM and natural language processing (NLP) published in 2013.Results: Four articles were selected, one focuses on Electronic Health Record (EHR) interoperability for clinical pathway personalization based on structured data. The other three focus on NLP (corpus creation, de-identification, and co-reference resolution) and highlight the increase in NLP tools performances.Conclusion: NLP tools are close to being seriously concurrent to humans in some annotation tasks. Their use could increase drastically the amount of data usable for meaningful use of EHR.
Keywords: Medical informatics; knowledge representation; natural language processing; semantic web; ontology